The urgency of protecting sensitive data is reflected in Article 4(2) of Law No. 27/2022 on Personal Data Protection - Andi Darti; M. Marnija (Warmadewa Press, 2025)
The protection of personal data is a top priority in the digital era, especially with the increasing threats to individual privacy and security of sensitive information such as health, biometric, and genetic data. Law No. 27 of 2022 concerning Personal Data Protection (PDP Law) is present as a legal framework that emphasizes the principles of transparency, security, and accountability to prevent data misuse. However, the implementation of the PDP Law in Indonesia faces significant challenges, such as technological limitations, low awareness among Electronic System Operators (PSEs), and weak law enforcement mechanisms. This study aims to analyze the effectiveness of Article 4(2) of the PDP Law in protecting sensitive data and explore strategic steps to overcome implementation constraints. The research methods used are normative research with juridical and conceptual approaches, as well as qualitative analysis. The juridical approach analyzes legal texts, while the conceptual approach explores the best practices of international regulations such as the EU GDPR. The data was analyzed descriptive-analytically to identify obstacles and solutions. The results of the study show that strengthening supervision, the adoption of advanced technologies such as AI and blockchain, and public education are urgently needed. This research recommends synergy between the government, PSE, and the community to create a safe and reliable digital ecosystem, while supporting digital transformation and sustainable economic growth.